PENGGUNAAN MEDIA PAPAN PERKALIAN UNTUK MENINGKATKAN PEMAHAMAN KONSEP PERKALIAN PADA SISWA KELAS II SD - Widayati, Ayu; Saragih, Mandra; Irvan, Irvan; Silalahi, Irayanti Masta M (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
This study aims to improve the understanding of multiplication concepts among second-grade students at SDN 060857 Medan through the use of a concrete instructional medium called the Multiplication Board, which integrates local cultural elements. The background of the research highlights the students’ low comprehension of basic multiplication concepts, as shown by the pre-cycle results where only 25% of students achieved mastery. This research is a Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The subjects of the study were 16 second-grade students. Data were collected through observation, interviews, and learning outcome tests. The results showed a significant increase in students’ understanding. Mastery learning rose from 25% in the pre-cycle to 43% in Cycle I, and then to 93% in Cycle II. These findings indicate that the Multiplication Board was effective in helping students understand multiplication concepts in a meaningful and contextual way. It also enhanced student engagement and interest in learning mathematics.